About Loss of Structural Stability during Movement of Multiphase Drilling Fluids - Ismayilov, G.G.; Veliyev, R.H.; Gulubayli, E.P. (Herald of Azerbaijan Engineering Academy, 2025)
The analysis of scientific research conducted in recent years shows that the drilling fluids used in the drilling of oil and gas wells can be described by rheological models. Currently, in most cases, these solutions are characterized by visco-plastic (pseudo-plastic) properties depending on the different basis and composition. Despite the above, considering the existence of the fact that they have structural stability and relaxation properties during the movement of drilling fluids and the importance and relevance of their attention, the article deals with the issues of rheological modeling of such systems and taking into account the violation of their structural stability. In the article, it is proposed to use the generalized exponential model for the description of oil-based drilling fluids in the presence of shear deformation. As a result of the rheological test of oil-based drilling muds of different composition on the basis of the mentioned model, the possibility of determining their structural stability coefficient and relaxation time has been shown.